National Study of Private Ownership of Firearms in the United States, 1994 ([Verlag nicht ermittelbar], 1998)
This data collection consists of a survey of private ownership of firearms by adults in the United States. Respondents who both did and did not own firearms were included. The variables cover topics such as the number and type of guns owned privately, methods of, and reasons for, firearms acquisition, the storage and carrying of guns, the defensive use of firearms against criminal attackers, and reasons for and against firearm ownership. Basic demographic variables include sex, age, education, and employment.